The Impact of Social Responsibility on Environmental Accounting (Companies Listed on the Tehran Stock Exchange) - Hashempour Abandansari, Mona; Abbasian, Mohammad Mehdi; PourAghajan, Abbas Ali; Ramezani , Aliakbar; Modanlo Joibary, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to investigate the impact of social responsibility on environmental accounting practices among companies listed on the Tehran Stock Exchange.Methodology: The research employed a descriptive-correlational design, focusing on a sample of 198 financial managers selected from a population of 589 through simple random sampling and Cochran's formula. Data were collected using a questionnaire and analyzed using SPSS version 25 and PLS version 3 for structural equation modeling. Both library and field methods were used for data collection.Findings: The results indicated that social responsibility significantly impacts environmental accounting, with a path coefficient of 0.401. The determination coefficient (R²) was 0.219, and the adjusted determination coefficient (R² Adjusted) was 0.213, indicating a moderate fit. The normality test showed that social responsibility data were normal, while environmental accounting data were not. Convergent and discriminant validity tests confirmed the reliability and validity of the measurement model.Conclusion: The study found a significant relationship between social responsibility and environmental accounting. Despite the importance of environmental costs, traditional accounting systems often neglect these costs. The adoption of environmental accounting practices can bridge the gap between environmental managers and accountants, enhancing both financial and environmental performance. Policymakers, managers, and regulators should consider integrating social responsibility into strategic planning and regulatory frameworks to promote sustainable business practices.